Community Service Skim Risma for School Year 2017 - Rizky Parlika; Didik Utomo Pribadi (Future Science)
In the country of Indonesia, especially in big cities like Surabaya, the need for education services is one of the most important things for the community. One form of educational services based on information technology that can run the school that is a complete package of educational applications. Complete education application will greatly support the learning and teaching process in school. In the year 2017 on our campus UPN “Veteran” of East Java, the Institute of Research and Community Service to open a community service scheme called Risma. Our Risma activities consist of two parts: first part we are training for teachers at SMP Catholic Santo Yusup Tropodo Waru Sidoarjo as our place to organize Risma activities. In the second phase, we started uploading the entire school application package into the hosting and domain services we rent and we manage to make the best use of it for the school. As a collection of Applications this school then we give name Risma for School Year 2017 which we short as RS 2017. RS 2017 consists of student absentee recap application, student recap, a recap of student guidance and counseling, student payment data recap, new student admission, and school profile web. The collaboration of all these applications into Integrated Education Information System that is ready to operate in schools in Indonesia. RS 2017 we have installed and settings on the risma2017.com domain page. On the web, risma2017.com will get articles that explain the training activities that we implement, the links to the implementation of the application and also a tutorial to run the application.